Nevus anemicus/Ischemic precursor of hemangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
Nevus anemicus is probably due to the persistent vasoconstriction within a localized skin area. As reported in the article of this issue regarding the precursors of hemangioma (1), an ischemic patch can be the first cutaneous sign of hemangioma. Nevus anemicus and precursor of hemangioma can be present at birth and should be differentiated from each other, also due to their different prognosis and evolution.